Pengaruh Analisis Rasio Keuangan Terhadap Financial Distress - Handoko Hadi; Eri Bukhari; Novita Wahyu Setyawati (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
This research uses data from transportation sector companies listed on the Indonesia Stock Exchange in the period 2017 2020. The aim of this research is to obtain empirical evidence regarding the influence of Liquidity (Current Ratio), Profitability (Return on Assets), Leverage (Debt to Assets Ratio) , and Operational Efficiency Ratio to Financial Distress. The data analysis method used is multiple linear regression analysis using SPSS Statistics Version 25. The research findings show that the Current Ratio partially has a significant and positive effect on financial distress. ROA partially has a significant and positive effect on Financial Distress. The Debt to Assets Ratio partially has a significant and negative effect on Financial Distress, and the Operating Efficacy Ratio partially has no effect on Financial Distress. Simultaneously the Current Ratio, Return on Assets, Debt to Assets Ratio, and Operational Efficiency Ratio have a significant and positive effect. The limitation of this research is that it does not include good corporate governance variables, company size to provide a more accurate picture or model. The practical implications of this research are that companies must optimize and maximize the management of current assets, current liabilities, total assets, total debt and operational costs to generate good profits.